2021
DOI: 10.3389/fonc.2021.644134
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Its Analogs: Potent Agents to Reverse Epithelial-to-Mesenchymal Transition in Tumors

Abstract: Epithelial-to-mesenchymal transition (EMT), a complicated program through which polarized epithelial cells acquire motile mesothelial traits, is regulated by tumor microenvironment. EMT is involved in tumor progression, invasion and metastasis via reconstructing the cytoskeleton and degrading the tumor basement membrane. Accumulating evidence shows that resveratrol, as a non-flavonoid polyphenol, can reverse EMT and inhibit invasion and migration of human tumors via diverse mechanisms and signaling pathways. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 162 publications
(180 reference statements)
0
22
0
Order By: Relevance
“…Moreover, we found that patients with high stromal and immune scores had shorter survival times, indicating that high-risk scores could predict a poor prognosis for HNSCC patients. This finding ultimately indicated that EMT could be related to the reconstruction of the tumor microenvironment while affecting tumor growth and progression (Li et al, 2020;Xu et al, 2021a;Guo et al, 2021;Lin et al, 2021). EMT is a critical event in the process of tumor metastasis, and our results support this conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, we found that patients with high stromal and immune scores had shorter survival times, indicating that high-risk scores could predict a poor prognosis for HNSCC patients. This finding ultimately indicated that EMT could be related to the reconstruction of the tumor microenvironment while affecting tumor growth and progression (Li et al, 2020;Xu et al, 2021a;Guo et al, 2021;Lin et al, 2021). EMT is a critical event in the process of tumor metastasis, and our results support this conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…Increasing evidence indicated that an important reason for CRC metastasis is the enhanced migration and invasion of cancer cells attributed to EMT phenotypes. EMT is a reversible and dynamic progression that transiently places epithelial cells into mesenchymal cells and affects the cellular architecture, which directly elevates tumor-initiating, invasive, and migratory characteristics (Dongre and Weinberg, 2019;Guo et al, 2021). Recently, numerous researches have confirmed that EMT progression is mainly mediated by multiple key signal transduction pathways containing transforming growth factor-β (TGF-β)/Smads, Wnt/β-catenin, phosphatidylinositol 3-kinase (PI3K)/Akt, Notch, and NF-κB signaling pathways (De Rosa et al, 2015;Vinson et al, 2016;Mishra et al, 2017;Tan et al, 2017;Song et al, 2020).…”
Section: Emt-related Signalings Involved In Metastasis Of Crc and Emt...mentioning
confidence: 99%
“…Research of the anti-metastatic effect of a large number of TCMs monomer compounds and Chinese medicine formulations based on TCM theory or coming from clinical experience have made considerable progress in recent decades. In this article, we mostly focus on certain bioactive compounds, natural herb extracts, and Chinese herbal recipes (Liu et al, 2018;Dai et al, 2019;Guo et al, 2021) repress the EMT program following their specific characteristics to inhibit the invasion and metastasis of CRC. Among them, there is a high proportion of investigations concentrated on TCMsoriginated monomers and compounds, while a small number of researches reported Chinese medicine formulas or medicinal herb extracts, as specifically shown in Tables 1-3, moreover, the chemical structure of the main TCMs active compounds with anti-metastatic and anti-invasive efficacies were exhibited in Figure 2.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Likewise, a natural methoxylated resveratrol analog has shown similar effects, inhibiting the proliferation, invasion, and migration of MCF-7 cells by down-regulating the PI3K/AKT and Wnt/β-catenin signaling pathways [ 94 ]. Additionally, resveratrol and its analogs revert EMT in tumors [ 95 ]. In T-47D BC cells, resveratrol has been shown to induce apoptotic cell death via caspase activation, CD95 ligand expression enhancement, and induction of CD95 signaling-dependent cell death, which initiates apoptosis [ 88 ].…”
Section: Combined Antitumoral Effect Of Calcitriol With Natural Compounds In Bcmentioning
confidence: 99%